Creating and capturing commerce : - Saloner, Garth (John Wiley & Sons, 2001)
The Stanford cases are written from the perspective of Silicon Valley, the heart of the e-commerce revolution. Authors are very involved in e-commerce companies, providing exceptional real world application and relevance.